Implementasi Model Pembelajaran Kooperatif STAD berbantuan Permainan Bingo untuk Meningkatkan Penguasaan Huruf Hiragana dan Katakana - Nathania Valmai Radoti; Desak Made Sri Mardani; Yeni Rahman (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to (1) improve the mastery of hiragana and katakana letters for class XII BB 2 students of SMA Negeri 4 Singaraja 2022/2023 Academic Year through the application of the Student Teams Achievement Division (STAD) cooperative learning model assisted by bingo games. and (2) describing students' perceptions of the implementation of the Student Teams Achievement Division (STAD) cooperative learning model assisted by bingo games to improve students' mastery of hiragana and katakana letters. This type of research is classroom action research which is carried out in two cycles consisting of three meetings in each cycle. The subjects in this study were students of class XII BB 2 SMA Negeri 4 Singaraja for the 2022/2023 academic year, which consisted of 36 students. Data collection methods used in this study were observation, tests, and questionnaires. The data that has been collected was analyzed quantitatively and descriptively. The results showed that (1) the implementation of the Student Teams Achievement Division (STAD) cooperative learning model was able to improve students' mastery of hiragana and katakana letters. This is evidenced by an increase in the percentage of completeness, namely, in the pre-test the percentage of completeness was 27.77%. Post-test cycle 1, experienced an increase of 80.55%. Then, there was another increase in the Post-test cycle II of 100%. (2) students' perceptions of the implementation of the Student Teams Achievement Division (STAD) cooperative learning model assisted by bingo games are classified as